Active curved surface deforming of flexible conformal electronics by multi-fingered actuator. (August 2020) - Chen, Jiankui; Yang, Sihui; Li, Yiqun; Huang, Yongan; Yin, Zhouping
Highlights: The active conformal deformation model based on least elastic potential energy is established and verified on the multi-fingered manipulator. An efficient and practical conformal deformation process that adapt to different target surfaces are designed. The proposed theoretical model and process are verified on real transfer printing platform made by us. Abstract: Flexible conformal electronics can be applied in many novel fields, such as wearable sensors, curved display and epidermal electronics, owing to their good adaptability to curved surfaces. Currently, the manufacturability of flexible electronics has been greatly enhanced with the development of various printing technologies. In this paper, the active conformal deformation model and device are presented under the framework of transfer printing. In particular, we present a practical deformation process of a multi-fingered actuator based on the minimization of elastic potential energy of the flexible membrane. The whole transfer printing platform as well as the multi-fingered manipulator are manufactured and the feasibility of them are verified with multiple tests on different target surfaces.